Implikasi UU Desa 2014 terhadap Tata Kelola dan Partisipasi Demokrasi - Dwi Pangestu, Rizki; Sumirat, Iin Ratna (Al-Daulah : Journal of Criminal Law and State Administration Law, 2025)
Research Objective: This study examines the effects of Law Number 6 of 2014 concerning Village Governance (the Village Law) on democratic perceptions and civic participation in Rahong Village, Malingping District, Lebak Regency, West Java Province. Research Method: Employing an empirical juridical approach within a qualitative research design, the study draws on primary data from semi-structured interviews with village officials, community leaders, and residents, supplemented by direct observation and document analysis. Results: The Village Law has positively reshaped citizens’ perceptions of the quality of local governance and established formal institutional channels for broader community participation in planning and decision-making. Findings and Implications: Implementation remains constrained by limited administrative capacity, insufficient transparency in budget management, accountability deficits, and uneven civic awareness, resulting in a participation gap between the law’s normative aspirations and observable democratic practice. Conclusion: While the Village Law has advanced grassroots democracy by devolving substantial authority to local communities, its full democratic potential remains unrealized due to persistent structural and capacity-related challenges. Contribution: This study provides original empirical evidence to scholarship on decentralization, democratic deepening, and the governance-participation nexus in rural Indonesia, with concrete implications for policy actions aimed at reinforcing village-level democracy. Limitations and Suggestions: The study is limited to a single-village context, which may limit generalizability. Future research should expand to multiple villages or districts and employ mixed-methods approaches to further validate and broaden these findings.